L’industrie minière et le développement urbain en milieu nordique : l’exemple de Fermont au Québec - Martin Simard; Carl Brisson (Cybergeo, 2013)
The map of Quebec show a vast peninsula of more than 1,6 million km2. However, the northern territories, successively called Ungava, New Quebec and North-of-Quebec, belong to that Canadian province since 1912. From a Quebecer point of view, the process of integration of these vast spaces sparsely inhabited by Inuit and First nation people was carried out late in history. Besides, the economic cycles related to the mining industry seem to deeply affect the development of these northern regions. Thus, stagnation and decline succeed periods of massive investments, which bring the installation of large facilities, megastructures and some human settlements. Fermont is one of these towns affected by economic cycles. That unique town was designed by the architect-planner Norbert Schoenauer, in 1972. It expresses a desire to adapt northern settlements to the cold climates. This paper aims at taking stock of this frontier town, forty years after its creation. We will address the issue of long-term development and resiliency of isolated mining communities in the context of the Quebec government renewed interest toward northern territories.